Cathepsin Inhibition Prevents Autophagic Protein Turnover and Downregulates Insulin Growth Factor-1 Receptor–Mediated Signaling in Neuroblastoma - Soori, Mehrnoosh (J Pharmacol Exp Ther, 2016)
Inhibition of the major lysosomal proteases, cathepsins B, D, and L, impairs growth of several cell types but leads to apoptosis in neuroblastoma. The goal of this study was to examine the mechanisms by which enzyme inhibition could cause cell death. Cathepsin inhibition caused cellular accumulation of fragments of the insulin growth factor 1 (IGF-1) receptor. The fragments were located in dense organelles that were characterized as autophagosomes. This novel discovery provides the first clear link between lysosomal function, autophagy, and IGF-1– mediated cell proliferation. A more in-depth analysis of the IGF1 signaling pathway revealed that the mitogen-activated protein kinase (MAPK) cell-proliferation pathway was impaired in inhibitor treated cells, whereas the Akt cell survival pathway remained functional. Shc, an adapter protein that transmits IGF-1 signaling through the MAPK pathway, was sequestered in autophagosomes; whereas IRS-2, an adapter protein that transmits IGF-1 signaling through the Akt pathway, was unaffected by cathepsin inhibition. Furthermore, Shc was sequestered in autophagosomes as its active form, indicating that autophagy is a key mechanism for downregulating IGF-1-induced cell proliferation. Cathepsin inhibition had a greater effect on autophagic sequestration of the neuronal specific adapter protein, Shc-C, than ubiquitously expressed Shc-A, providing mechanistic support for the enhanced sensitivity of neuronally derived tumor cells. We also observed impaired activation of MAPK by epidermal growth factor treatment in inhibitor-treated cells. The Shc adapter proteins are central to transducing proliferation signaling by a range of receptor tyrosine kinases; consequently, cathepsin inhibition may become an important therapeutic approach for treating neuroblastoma and other tumors of neuronal origin.